2013
DOI: 10.1088/2041-8205/779/1/l7
|View full text |Cite
|
Sign up to set email alerts
|

SOLAR DYNAMICS OBSERVATORY/ATMOSPHERIC IMAGING ASSEMBLY OBSERVATIONS OF A REFLECTING LONGITUDINAL WAVE IN A CORONAL LOOP

Abstract: We report high resolution observations from the Solar Dynamics Observatory/Atmospheric Imaging Assembly (AIA) of intensity oscillations in a hot, T ∼8-10 MK, loop. The AIA images show a large coronal loop that was rapidly heated following plasma ejection from one of the loop's footpoints. A wave-like intensity enhancement, seen very clearly in the 131 and 94Å channel images, propagated ahead of the ejecta along the loop, and was reflected at the opposite footpoint. The wave reflected four times before fading. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 36 publications
(41 reference statements)
9
60
0
2
Order By: Relevance
“…In numerical experiments, Fang et al (2015) found that these flows result in periodic emission in the footpoints, and can be directly observed in the flare loop body (confirming the interpretation of the observations of Kumar, Innes, and Inhester, 2013;Kumar, Nakariakov, and Cho, 2015). Moreover, such a mechanism may be responsible for the standing slow waves observed in hot flare loops with SUMER (Wang, 2011;Yuan et al, 2015).…”
Section: Mhd Waves In Flaring Systemsupporting
confidence: 58%
“…In numerical experiments, Fang et al (2015) found that these flows result in periodic emission in the footpoints, and can be directly observed in the flare loop body (confirming the interpretation of the observations of Kumar, Innes, and Inhester, 2013;Kumar, Nakariakov, and Cho, 2015). Moreover, such a mechanism may be responsible for the standing slow waves observed in hot flare loops with SUMER (Wang, 2011;Yuan et al, 2015).…”
Section: Mhd Waves In Flaring Systemsupporting
confidence: 58%
“…In contrast, in the other case with the classical thermal conduction and viscosity coefficients, the scaling relation between the decay time and the period is linear, and a timescale of several reflections is required for the initial propagating disturbance to form the standing wave pattern. This latter loop model may explain the reflected propagating feature of a longitudinal wave event reported in Kumar et al (2013).…”
Section: Discussionmentioning
confidence: 76%
“…Like the SUMER oscillation events (e.g. Wang et al 2005), the initiation of the AIA longitudinal waves is also associated with small flares (GOES B or C-class) at the loop footpoint (Kumar et al 2013(Kumar et al , 2015Wang et al 2015;Nisticó et al 2017). Magnetic extrapolation and emission features suggest that the confined flares are produced by reconnections at a coronal null point in a fan-spine magnetic topology Kumar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If one suggests the modulation by MHD waves, a plausible step is to correlate the timestamps in integrated light curves and periodic waves. A series of studies was done on modulation by standing and reflective slow mode waves (Wang et al 2003a,b;Wang 2011;Kumar et al 2013Kumar et al , 2015Yuan et al 2015;Fang et al 2015;Mandal et al 2016). Most previous studies focus on a good match of periodicity and phase difference.…”
Section: Introductionmentioning
confidence: 99%